2018
DOI: 10.21037/jtd.2017.12.32
|View full text |Cite|
|
Sign up to set email alerts
|

Pulmonary embolism concurrent with lung cancer and central emboli predict mortality in patients with lung cancer and pulmonary embolism

Abstract: Background: Patients with lung cancer commonly experience pulmonary embolism (PE). The aim of the present study was to examine the clinical features of patients with lung cancer and PE and to investigate prognostic factors in these patients. Methods: This retrospective study divided patients with lung cancer and PE into a group of patients with PE diagnosed concomitantly with lung cancer (concurrent group) and a group with PE detected after lung cancer (sequential group), compared the clinical characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
(39 reference statements)
1
16
0
1
Order By: Relevance
“…As these studies are very heterogeneous in methodologies and study cohorts, comparisons across studies are not feasible. As with Western studies, this review found that VTE-related deaths (range 0.7-4.2%) were mostly associated with PE and mostly from hospital-based studies (27)(28)(29)39). However, the interpretation of mortality findings was complicated by varying ways of mortality reporting over various timeframes.…”
Section: Impact Of Vte In Cancer Patients: Morbidity Mortality and Recurrencesmentioning
confidence: 89%
See 2 more Smart Citations
“…As these studies are very heterogeneous in methodologies and study cohorts, comparisons across studies are not feasible. As with Western studies, this review found that VTE-related deaths (range 0.7-4.2%) were mostly associated with PE and mostly from hospital-based studies (27)(28)(29)39). However, the interpretation of mortality findings was complicated by varying ways of mortality reporting over various timeframes.…”
Section: Impact Of Vte In Cancer Patients: Morbidity Mortality and Recurrencesmentioning
confidence: 89%
“…Four studies reported VTE-related deaths (mostly associated with PE). The three large-scale studies with VTE-related deaths reported rates ranging from 0.7-3.3% (27)(28)(29) whereas one small-scale prospective cohort study of newly diagnosed NSCLC patients reported a 4.2% VTE-related mortality rate (39). Three large-scale studies reported all-cause mortality rates from 7.5 to 63.9% (26,28,31) while the rates reported by three small-scale studies were from 9.7 to 78.3% (25,35,41).…”
Section: Rates Of Vte In Cancer Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Median period of time from diagnosis of lung cancer to PE was 4,5 months. The most common risk factor for pulmonary embolism in patients with lung cancer was chemotherapy with even a 3-fold increased risk [14]. 4.).…”
Section: Risk Factors Paediatric Patientsmentioning
confidence: 99%
“…Different risks of thrombosis in four coagulation defects associated with inherited thrombophilia. Cancer is one of the most relevant risk factors for VTE, which occurs two to four times more often in patients with diagnosed malignancy.The highest prevalence of venous thromboembolism include lung, colon, and prostate cancer, whereas lung cancer is the most commonly related malignancy in patients with VTE[11][14]. According to data delivered by European Heart Journal Guidelines published in 2014, risk of venous thromboembolism episodes in patients with cancer is relevantly higher (even 46-fold comparing to healthy controls).…”
mentioning
confidence: 99%